Biotreatment of High Fat and Oil Wastewater by Lipase Producing Microorganisms - Orapin Bhumibhamon; Achara Koprasertsak; Suptawee Funthong (Agriculture and Natural Resources, 2002)
Studies on biotreatments of high fat and oil wastewater by selected lipase producing bacteria were carried out in two experiments with two groups of bacteria, single culture and mixed culture. In the first experiment, wastewater of bakery industry was treated with 4 bacteria isolates. Results showed that grease in the form of fat and oil and COD decreased remarkably with treatments. With single culture, the removal of fat and oil and COD were 73%-88% and 81%-99% during 7 days treatment. Isolates KUL8 and KUL39 showed better activities. However, better treatments were found in experiment treated with single culture than using mixed culture. In the second experiment, wastewater of palm oil and bakery industries were treated with 6 isolates within 48 hours. All 6 isolates showed better degradation in palm oil wastes than bakery wastes. However, KUL8 and KUL39 still showed better degradation activities. Both isolates can removed fat and oil by 87.7% and 80.6% in palm oil wastewater and 70% and 64% in bakery wastes respectively. The decreasing of COD was found to be 90%-96%. When mixed culture of KUL8, KUL39 and KLB1 were applied for both kinds of wastewater. It was found that better results were observed in palm oil treated with single culture KUL8, KUL39, and KUB1 while mixed culture KUL8 mixed with KLB1 was suitable for use in bakery waste. The three isolates were identified as Acinetobacter sp. (KUL8), Bacillus sp. (KUL39), and Pseudomonas sp. (KLB1). They were all mesophilic strains. Besides, it was found that all three strains also produced amylase and protease which stimulate better waste treatments.